Acid-promoted furan annulation and aromatization: An access to benzo[b]furan derivatives. Issue 4 (25th January 2018) - Ao, Jun; Liu, Yidong; Jia, Shiqi; Xue, Lu; Li, Dongmei; Tan, Yu; Qin, Wenling; Yan, Hailong
Abstract: An unprecedented PTSA-promoted furan annulation and aromatization in one pot has been developed. This process offers a simple and efficient synthetic route for the construction of various highly substituted benzo[ b ]furan derivatives, which are widely used not only in drug active molecules but also organic semiconductor and organic light-emitting devices. The preliminary mechanism study indicated this transformation proceeded sequentially via furan annulation and aromatization. Graphical abstract: